Instalasi Pengolahan Air Limbah Rumah Sakit Umum Daerah Provinsi Nusa Tenggara Barat - Jupri, Ahmad; Putri, Nurliana Hasan; Supardiono, Supardiono; Ahyadi, Hilman; Hidayati, Lilik (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2025)
Wastewater management in hospitals is an important aspect to maintain environmental quality and public health. This research evaluates the effectiveness of the Waste Water Treatment Plant (IPAL) at the Regional General Hospital of West Nusa Tenggara Province (RSUDP NTB) using a biofilter system. The research was conducted for 30 days with a focus on operational observations, interviews with staff, and analysis of wastewater treatment data. The results show that the NTB RSUDP WWTP consists of seven units with varying capacities and involves pre-processing and main processing stages. Despite comprehensive operations, challenges such as pipe blockages and problems with flow meters still occur. Recommendations include improving routine maintenance, optimizing processing processes, and outreach regarding solid waste disposal.